PEMANFAATAN BUAH MANGGA (MangiferaindicaL.) DAN EKSTRAK TEH HIJAU (Cameliasinensis) DALAM PEMBUATAN SELAI - Sibuea, Anggi Febrian; Hamzah, Faizah; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to know the effect of level mixing of mango porridge and green tea extracts to chemical analysis and organoleptic test of jam. This research used Complete Randomized Design (CRD) with four treatments and four replications, which followed by Duncan’s NewMultiple Range Test (DNMRT)at level 5%. The treatments were MT1 (100 mango porridge : 0 green tea extracts); MT2 (90 mango porridge : 10 green tea extracts); MT3 (80 mango porridge : 20 green tea extracts) andMT4 (70 mango porridge : 30 green tea extracts). The result of analysis showed that the level mixing of mango porridge and green tea extracts significantly effect on moisture content, pectin content, sucralose content, pH, descriptive of color, aroma, taste and texture and then hedonic of color and taste. The level mixing of mango porridge and green tea extract had notsignificantly effect onhedonic of aroma and texture.The best treatment was MT2 with moisture content 21,48; pectin content 1,50; sucralose content 56,65; and pH 3,31. Key word : Mango, Green tea, Mango and green tea jam.